2021
DOI: 10.3390/jcm10215060
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlations in Relation to Newly Emerging Monogenic Forms of Autism Spectrum Disorder and Associated Neurodevelopmental Disorders: The Importance of Phenotype Reevaluation after Pangenomic Results

Abstract: ASD genetic diagnosis has dramatically improved due to NGS technologies, and many new causative genes have been discovered. Consequently, new ASD phenotypes have emerged. An extensive exome sequencing study carried out by the Autism Sequencing Consortium (ASC) was published in February 2020. The study identified 102 genes which are de novo mutated in subjects affected by autism spectrum disorder (ASD) or similar neurodevelopmental disorders (NDDs). The majority of these genes was already known to be implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The introduction of WES in the genetic diagnosis of ASD has significantly improved our knowledge of its etiology at the molecular level. The phenotype-driven analysis is often a limitation in the discovery of new disease-associated genes since the clinical presentation of patients with ASD is a key factor in genetic testing and data interpretation ( Arteche-López et al, 2021 ; Lintas et al, 2021 ). The process of establishing an accurate diagnosis is further hindered by the lack of segregation analysis, reduced penetrance, limited data availability in the literature, as well as non-specific and limited clinical descriptions of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of WES in the genetic diagnosis of ASD has significantly improved our knowledge of its etiology at the molecular level. The phenotype-driven analysis is often a limitation in the discovery of new disease-associated genes since the clinical presentation of patients with ASD is a key factor in genetic testing and data interpretation ( Arteche-López et al, 2021 ; Lintas et al, 2021 ). The process of establishing an accurate diagnosis is further hindered by the lack of segregation analysis, reduced penetrance, limited data availability in the literature, as well as non-specific and limited clinical descriptions of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The process of establishing an accurate diagnosis is further hindered by the lack of segregation analysis, reduced penetrance, limited data availability in the literature, as well as non-specific and limited clinical descriptions of patients. Therefore, reverse phenotyping and seeking the ultrarare variants in genes that are not only limited to ASD and then performing functional studies to obtain datasets should result in a higher diagnostic yield ( Lintas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations are in line with a recent caregiver report on the characteristics of patients diagnosed with KDM5C variants [ 1 ]: all females had developmental delay and language impairment, 60% had intellectual disability, 70% had short stature, 56% had aggressive behavior, and 44% had anxiety disorder. The clinical geneticist should be aware of these specific clinical features, especially when attempting the interpretation of more variants emerging from WES analysis [ 22 ]. Indeed, reverse phenotyping has become a very useful approach in clinical genetics following the routine implementation of pangenomic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many published case study descriptions of NDDs, which are identified on the basis of a genomic event (for a review, see [ 59 ]), do not mention the presence of motor speech disorders because they fail to include in the clinical team speech pathologists with the appropriate diagnostic expertise. Instead, most of what we know comes from studies that ascertained cases with motor speech deficits and then carried out genetic testing or were designed to investigate speech in specific genetic cohorts.…”
Section: Genes Associated With Motor Speech Disorders In Nddsmentioning
confidence: 99%